Hubungan Status Gizi terhadap Kualitas Hidup pada Pasien Penyakit Ginjal Kronik yang Menjalani Hemodialisis di RSUD Arifin Achmad Provinsi Riau - ligat pribadi sembiring; zulfa nur hanifah (Jurnal Ilmu Kedokteran, 2020)
This research was conducted to investigate the relationship between nutritional status and quality of life in CKD patients with hemodialysis at Arifin Achmad Regional Hospital. The design of this research was an analytic study with a cross-sectional approach that obtained primary data from the questionnaire. Based on inclusion and exclusion criteria, showed the total cases were 54 cases, mostly suffered by men(56%) with an age group 45-64 years by 74.5%. An assessment of medical conditions obtained by 54% of respondents had a duration of hemodialysis>12 months with 74% had a reduction of weight in a varying range. Assessment nutritional status with SGA-DMS questionnaire showed malnutrition results (84%) and assessment quality of life with KDQOL-SF36 questionnaire showed the good quality of life results (57%). The bivariate analysis used Pearson-Chi-Square with p=0.003. Conclusion there was a significant relationship between nutritional status and quality of life in CKD patients with hemodialysis at Arifin Achmad Regional Hospital.